daca a+b+c =17 a+c=11 iar b×(c-a)=42,atunci a=?b=?c=?
Răspunsuri la întrebare
Răspuns de
0
Răspuns:
2, 6, 9
Explicație pas cu pas:
a+b+c=17
a+c=11
b=17-11
b=6
b*(c-a)=42
6*(c-a)=42
c-a=42:6
c-a=7
c=a+7
a+c=11
a+7+a=11
2a+7=11
2a=11-7
2a=4
a=2
c=2+9
c=9
Răspuns de
0
Răspuns:
Explicație pas cu pas:
b=17-11=6 ; 6(c-a)=42 ; c-a=7 ; c+a=11 ; se aduna ; 2c=18 ; c=9 ; a= 11-9=2 ;
Alte întrebări interesante
Matematică,
8 ani în urmă
Engleza,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Istorie,
9 ani în urmă
Matematică,
9 ani în urmă